How to Write Technical Reports Understandable Structure, Good Design, Convincing Presentation - Hering, Heike (Springer Berlin Heidelberg : Imprint: Springer, 2019)
The 2nd edition was fundamentally changed and adopted to be displayed not only in book form, but also on all kinds of electronic devices. The following sections have been reduced or skipped: Tables, Scheme and diagram, Perspective drawing, Technical drawing and bill of materials, Pictorial re-arrangement of text, Copyright and copyright laws, Details about text accentuation, Automatic creation of indexes, tables, lists, labels and cross-references, Creating slides with presentation graphics programs.